Ratification Of Marriage Agreement After The Enforcement Of The Constitutional Court Decision Number 69/PUU-XIII/2015 In Accordance With The Principle Of Authentication - Laila Yunita; Suprapto Suprapto (JURNAL HUKUM SEHASEN, 2024)
In social life, humans are always attached to each other, unable to live alone. They go through various legal events, such as birth, death, and marriage. Marriage, as a physical and inner bond between a man and a woman, aims to form a happy family based on the One Godhead. In this context, husband and wife have clear rights and obligations. Apart from being a legal act, marriage is also a religious act that refers to the teachings of their respective religions. Legally, marriage is defined as a life with a man and a woman who meet certain conditions. The Constitutional Court has given new authority to notaries to ratify marriage agreements, an aspect that is not regulated in the Notary Office Law (Law 2/2014). However, this agreement only binds the parties who drafted it, and to bind third parties, it is necessary to have a publication principle that allows the information to be known to the public. The concept of this publication is contrary to the principle of notary confidentiality regulated in Article 16 and Article 54 of Law 2/2014, which emphasizes the obligation of notaries to keep information confidential. Therefore, the application of the principle of authentication in marriage agreements is important to ensure legal validity. The agreement must be made in the form of an authentic deed to be valid, in accordance with the provisions of the applicable law. This article aims to explore these dynamics and their implications in legal practice in Indonesia.